2013
DOI: 10.1111/jgh.12237
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hyperphosphatemia significantly associates with adverse survival in colorectal cancer patients

Abstract: Background Hyperphosphatemia has been implicated in the development and treatment of various cancers. However, whether it can be used as a direct prognostic marker of colorectal cancer (CRC) has remained unexplored. Given new insights into the importance of hyperphosphatemia in CRC, we sought to evaluate the association of hyperphosphatemia with the clinical outcomes of this disease. Methods In a retrospective analysis of a well-characterized clinic-based cohort with 1,241 CRC patients, we assessed the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…32 In contrast, Ye and colleagues in their recent report of patients undergoing surgery for colorectal cancer demonstrated postoperative hyperphosphatemia to be associated with poor long-term clinical outcomes. 33 Of note, these authors suggested that the impact of hyperphosphatemia was relative to a wide inhibitory effect on signaling transductions protein kinase-mediated signaling pathways in the whole body and not restricted only to CRC-specific mechanisms. In the current study, although no correlation between serum phosphorus and postoperative morbidity was observed, patients who developed hyperphosphatemia on the second postoperative day had a worse long-term survival (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…32 In contrast, Ye and colleagues in their recent report of patients undergoing surgery for colorectal cancer demonstrated postoperative hyperphosphatemia to be associated with poor long-term clinical outcomes. 33 Of note, these authors suggested that the impact of hyperphosphatemia was relative to a wide inhibitory effect on signaling transductions protein kinase-mediated signaling pathways in the whole body and not restricted only to CRC-specific mechanisms. In the current study, although no correlation between serum phosphorus and postoperative morbidity was observed, patients who developed hyperphosphatemia on the second postoperative day had a worse long-term survival (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The significantly higher P level in cancerous patients compared to the other two groups maybe the sign of cell death, because hyperphosphatemia is also a signal of the rare but life threatening case, the tumor lysis syndrome (Kim 2014). The importance of P concentration is discussed in surgical cases, and in the future may become a crucial prognostic factor (Ye 2013). Zn concentration has changed diversely in the two patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…multiple myeloma) may be accompanied by hyperphosphatemia [35]. An increase in serum phosphorus level can be observed as a result of tumour treatment [36][37][38]. A significant increase in serum phosphorus after tumour removal is a poor prognostic factor for patient survival [38].…”
Section: Phosphorus (Phosphate)mentioning
confidence: 99%
“…An increase in serum phosphorus level can be observed as a result of tumour treatment [36][37][38]. A significant increase in serum phosphorus after tumour removal is a poor prognostic factor for patient survival [38]. Often, hyperphosphatemia is a typical sign of tumour lysis syndrome [39][40][41][42] and was proposed as one of the criteria of the laboratory tumour lysis syndrome diagnosis [43].…”
Section: Phosphorus (Phosphate)mentioning
confidence: 99%
See 1 more Smart Citation